1954
DOI: 10.1001/archneurpsyc.1954.02320370068005
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Changes in Neurons, Neuroglia, and Blood-Brain Barrier Induced by X-Irradiation of Heads of Monkeys

Abstract: IN COMPARISON with the severe changes seen in many tissues, reports concerning the effects of ionizing radiation on the adult central nervous system have usually indicated a relative radioresistance on the part of the brain.* This observation is supported by experiments suggesting that sensitivity to irradiation depends in part on the rate of synthesis of nucleic acids, the lymphocyte and the maturing neuroblast appearing more radiosensitive than the adult neuron.5 Despite these general statements, reports fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1954
1954
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Macroscopic observation detected more extravasated serum albumin in the gray matter than in the white matter. The cause of this difference is not clear, but may be related to the larger capillary volume in the gray matter than in the white matter (corpus callosum) [6]. This distribution between gray and white matter differs from the distribution of oedema fluid seen in brain tumours, cerebral ischaemia and cold injury [1,12,21].…”
Section: Discussionmentioning
confidence: 98%
“…Macroscopic observation detected more extravasated serum albumin in the gray matter than in the white matter. The cause of this difference is not clear, but may be related to the larger capillary volume in the gray matter than in the white matter (corpus callosum) [6]. This distribution between gray and white matter differs from the distribution of oedema fluid seen in brain tumours, cerebral ischaemia and cold injury [1,12,21].…”
Section: Discussionmentioning
confidence: 98%
“…Ultrastructurally, endothelial cell changes and proliferation are present [16,17]. Delayed radiation encephalopathy includes parenchymal foci of necrosis, particularly of white matter, or demyelination with rela tive preservation of axons as well as the vasculopathy mentioned above [18][19][20][21][22][23][24], Experimentally, metabolic rates of some brain structures are reduced following moderate doses of x-radiation [25]. Whether or not radi ation leukoencephalopathy is related to vascular abnor malities, a number of reports have appeared suggesting that protection of the microcirculation may be possible [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings do not disclose whether the effects are to be attributed to the physical characteristics of neutrons as opposed to other forms of ionizing radiation, or to one or another of the conditions of exposure, notably the energy, the dose, or the dose rate. Many observations have shown that x-ray and gamma radiation produce areas of necrosis in the grey and white matter of the brain; but these lesions are regularly associated with marked vascular sclerosis, and they have generally been attributed to ischemia (10)(11)(12). A degeneration of the cerebral tissues has been noted, however, in the absence of conspicuous changes in the blood vessels, in animals exposed to 23 mev.…”
Section: Discussionmentioning
confidence: 99%